Vignettes in Patient Safety - Volume 4 [Working Title] 2019
DOI: 10.5772/intechopen.84530
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive and Live Air Purification as a Key Environmental, Clinical, and Patient Safety Factor: A Prospective Evaluation

Abstract: Healthcare organizations strive to provide optimal patient experience by improving care quality and enhancing clinical outcomes, while containing associated costs. In the United States, the Center for Disease Control (CDC) estimates that more than 1.7 million people suffer from an infectious complication annually, representing between 5 and 10% of all hospital admissions and costs ranging between $35B and $88B. Most infectious surface fomites originate from air. Consequently, reducing airborne pathogens should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The kill ability provided by this technology was intentional as the capture ability employed by standard hospital high-efficiency particulate arrestance (a.k.a., HEPA) filtration systems, the most common means of air filtration used in healthcare, cannot provide comprehensive remediation when pathogen sizes fall within the range of 0.1–0.3 μ. [ 586 ] The approximate size of SARS-CoV-2 is 0.125 μ. [ 587 ] Because the HEAFT comprehensively remediates the COVID-19 airborne virus, it may be useful in hospitals, nursing facilities, critical care infrastructure, and frontline modular containment/isolation areas, to protect patients, HCWs, and those in potential proximity to infected individuals (e.g., contractors, visitors/families, nonclinical personnel, and allied healthcare professionals).…”
Section: E Nvironmental P Arameter mentioning
confidence: 99%
“…The kill ability provided by this technology was intentional as the capture ability employed by standard hospital high-efficiency particulate arrestance (a.k.a., HEPA) filtration systems, the most common means of air filtration used in healthcare, cannot provide comprehensive remediation when pathogen sizes fall within the range of 0.1–0.3 μ. [ 586 ] The approximate size of SARS-CoV-2 is 0.125 μ. [ 587 ] Because the HEAFT comprehensively remediates the COVID-19 airborne virus, it may be useful in hospitals, nursing facilities, critical care infrastructure, and frontline modular containment/isolation areas, to protect patients, HCWs, and those in potential proximity to infected individuals (e.g., contractors, visitors/families, nonclinical personnel, and allied healthcare professionals).…”
Section: E Nvironmental P Arameter mentioning
confidence: 99%
“…The background environmental metrics used by the research team to compare AHU-HEPA and AAPT were published previously and examined prospectively, with detailed methodologic descriptions outlined in a separate manuscript. 17 Of note, the earlier publication evaluated overall airborne bacterial and fungal loading and included microbial testing of 3 commonly touched patient surfaces and 2 commonly touched clinical surfaces, with additional swabbing of air supply diffusers and return vents for viable bacteria and fungi. 17 The current study was based on a subset of nonbariatric surgical patients with an inpatient admission to any of the 3 zones who had a case mix index (CMI) included in their electronic medical record at the time of discharge (N ¼ 1,002).…”
Section: Methodsmentioning
confidence: 99%
“…16 Previous experience with the advanced air purification technology (AAPT) demonstrated that comprehensive remediation of airborne pathogens resulted in a decrease in infectious fomites across a variety of patient-facing surfaces. 17 The AAPT used in this study is more efficient than most current methods of air filtration in the hospital setting. 18 Operationally, the AAPT replaces a section of the hospital's existing heating ventilation and air conditioning ductwork and utilizes ultraviolet, germicidal irradiation technology and a multireflective enclosure to provide continuous, real-time remediation of all airborne pathogens before the air entering areas of patient care.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, consideration of design, equipment, and ventilation is important. [ 10 12 ] Incorporating negative-pressure rooms/areas into health-care facility designs, whether natural or mechanical, serves to dilute droplet nuclei in the air. This seems to be the single-most important engineering control for the successful reduction of airborne infection transmission.…”
Section: Introduction : C Hanges Since S Evere a Cute R Espirmentioning
confidence: 99%